2020
DOI: 10.1038/s41598-020-79059-7
|View full text |Cite
|
Sign up to set email alerts
|

Minimum effective volume of ropivacaine for ultrasound-guided supra-inguinal fascia iliaca compartment block

Abstract: Supra inguinal fascia iliaca compartment block (FICB) is increasingly used in elderly patients with hip fractures. However, the minimum effective volume of local anesthetics required for ultrasound-guided supra-inguinal FICB has not been determined. With ethical committee approval and written informed consent from patients, we studied 21 consecutive patients of ASA physical status I–III undergoing surgery for hip fracture who met the inclusion criteria. Blocks were performed before going to the operation room.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Yamada et al . [ 24 ] studied the minimum effective volume of LA in S-FICB. They found that the EV50 and EV95 of 0.25% ropivacaine for S-FICB were 15.01 ml and 26.99 ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al . [ 24 ] studied the minimum effective volume of LA in S-FICB. They found that the EV50 and EV95 of 0.25% ropivacaine for S-FICB were 15.01 ml and 26.99 ml, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a cadaver study, Kris Vermeylen et al reported that 40 mL of local anesthetic was required to stain the femoral, lateral femoral cutaneous, and obturator nerves in adult cadavers by supra-inguinal FICB [21]. The study by Kumiko et al showed that the EV95 of 0.25% ropivacaine in suprainguinal FICB for blocking all three nerves was 27.0 mL [22]. We used 30 mL of analgesic in our clinical trial and demonstrated that the supra-inguinal approach was superior to the classical approach when evaluating sensory block in the obturator and lateral femoral cutaneous nerves.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous cadaveric and clinical reports. Yamada et al (2020) demonstrated that the 50 % and 95 % effective volume of 0.25 % ropivacaine for the USG-SFIB was 15 and 27 ml. The definition of a successful block in that study was a loss of sensation of the LFCN and FN sensory distribution.…”
Section: Discussionmentioning
confidence: 94%